Analisa Perbandingan SAW, WP, dan TOPSIS Dalam Penentuan Siswa Terbaik - Moch Agung Maulana; Adelia Dewi; Fadly Krisna; Imam Wahyu Julianto; Perani Rosyani (CV. Multi Kreasi Media, 2023)
Schools play an important role in advancing the quality of education in Indonesia, one of the efforts being made is to utilize information technology. an award system for the best students in the school environment is a good strategy in fostering students' motivation to study and excel in both academic and non-academic fields. This research aims to help the school, such as the principal and the teachers who teach in determining the best students in school. In determining student achivement a decision support system will be made using the Simple Additive Weighting (SAW) method, the Weighted Product (WP) method and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS).To determine outstanding students there are 5 criteria, namely Discipline, Morals, Highest Report Card Score, Absence, and Extracurricular Value with 5 alternatives and 5 weights for each criterion. Based on the results of analyzing and processing the data, different rankings are produced for each method, even so there are still some things that produce the same data, such as the three methods which produce the same 1st and 2nd rankings. The resulting ranking equation is triggered by the influence of alternative performance scores, and the weight value of the criteria applied to each method.